Fermi GBM Observations of the Galactic Magnetar SGR 1935+2154 during Its 2022 January Activity - Noor ul Sabah Rehan; Alaa I. Ibrahim (The Astrophysical Journal, 2024)
The X-ray and radio burst-emitting soft gamma-ray repeater SGR 1935+2154 has been the most active magnetar during the past decade, with at least one active episode each year since 2019. We report on the 2022 January activity as observed by the Fermi Gamma-Ray Burst Monitor and present the temporal and time-integrated spectral properties of the observed 112 X-ray bursts. No radio bursts were reported during the activity. The mean burst duration is comparable to most of the previous activities but is shorter than that of 2020, during which the magnetar emitted radio bursts. The mean burst spectrum is softer than the earlier activities and a long-term softening trend since 2016 is evident and is accompanied by a rise in the mean burst fluence and blackbody emission radii. The power-law indices of the ${R}_{BB}^{2}-{{kT}}_{BB}$ correlation also show an evolution during 2019–2022, where the soft component started becoming steeper, whereas the hard component shows a less steep trend. The burst properties show no significant evolution within the activity, which lasted for ∼ 45 days, and none of the observed bursts showed properties reminiscent of those of the hard, long X-ray counterpart to the 2020 fast radio burst FRB 200428 from the source. We discuss the results comparatively with the 8 yr history of the source since its discovery in 2014.